Comorbidities and Cardiovascular Disease Risk in Older Breast Cancer Survivors - Haque, Reina (2014)
OBJECTIVE: To evaluate cardiovascular disease (CVD) risk factors in older breast cancer survivors compared with a group of women without breast cancer. STUDY DESIGN: The retrospective study included (1) women aged 65 or more years who were initially diagnosed with stage I or II breast cancer from 1990 to 1994 in 6 US health plans and who survived at least 5 years postdiagnosis (cases) and (2) a matched comparison group. They were followed for a maximum of 15 years. METHODS: Data sources included medical charts and electronic health records. Cases (n = 1361) were matched on age, health plan site, and enrollment year to women in the comparison group (n = 1361). Subjects were followed to the first CVD outcome, health plan disenrollment, death, or study end. We compared rates of CVD in these 2 groups and used Cox proportional hazard models to estimate the hazard ratio (HR), considering body mass index, smoking history, diabetes, and hypertension. RESULTS: The strongest predictors of CVD were smoking history (HR = 1.29; 95% confidence interval [CI], 1.15–1.46), diabetes (HR = 1.72; 95% CI, 1.48–1.99), and hypertension (HR = 1.48; 95% CI, 1.31–1.67) rather than breast cancer case-comparison status (HR = 0.97; 95% CI, 0.87–1.09). CONCLUSION: Results suggest that long-term prognosis in breast cancer patients is affected by management of preexisting conditions. Assessment of comorbid conditions and effective management of diabetes and hypertension in older breast cancer survivors may lead to longer overall survival.